PEMISAHAN KARBON TIDAK TERBAKAR DARI ABU TERBANG DENGAN MENGGUNAKAN SISTEM DISSOLVED AIR FLOTATION (DAF) UNTUK MENINGKATKAN KUALITAS ABU TERBANG - Vherlly Surjaatmadja; Winandyo Mangkoto; Setia Budi Sasongko (JURNAL TEKNOLOGI KIMIA DAN INDUSTRI, 2013)
Fly ash is a solid waste product of  coals combustion. Potential areas for the utilization of fly ash is in cement production, butthe unburned carbon in fly ash adversely affects the quality of final product (Miura, K 2010), and this research is a way to separate unburned carbon from fly ash using a flotation column with DAF system(Dissolved Air Flotation). This research is also aim to calculate the unburned carbon using LOI test (Lost On Ignition). This method, used to calculate unburned carbon content, will estimate energy potential from  fly ash recycles.The variable that used in this research is flotation times (15, 25, 35, 45, and 55) minutes and feed concentrations (10, 20, 30, 40, 50) gram/liter. The result shows that the biggest of average % reduction of LOI is 55.1782% at 55 minutes of time variable. For concentration variable there is no significant differences because the average % differences is 7.5395%. Therefore the most effective variable in this research is 50 gram/liter of concentrations and 55 minutes of flotation times.